Proposed Marketing Strategy for Telkom STARBox - Astiana Soejarno, Hanna; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2016)
Abstract – The progression of the use of the internet in Indonesia opens an opportunity to MSMEs to develop its business. Therefore, Telkom launched STARBox as business solution to MSMEs to expand their business by going online. However, despite the great potential, the sales of STARBOX have not shown the good results. There is the underachievement of the sales target. This study then intended to seek an effective marketing strategy for Telkom to meet STARBox sales target. SWOT analysis has shown that there is a low awareness regarding STARBOX. Low customer awareness due to the low activity of marketing and limited distribution channels. The utilization of integrated marketing communications and widening the distribution channels used to address the root of the problem. The IMC plan offered in two option depend on the Telkom’s marketing budget for STARBox and will be evaluated once per six months by receive continuous feedback on what has been done, both from the internal management and consumers. The IMC plan and the expansion of distribution channel are scheduled to be carried out within a one year period. Keywords: marketing strategy, integrated marketing communications, broadband, e-commerce, MSMEs